Vulvar Lymphangiosarcoma in a Bitch - Fabris, Isabella de Almeida; de Farias, Marconi Rodrigues; Werner, Juliana; Albernaz, Vinicius Gonzales Peres; Fuchs, Taíse; Miara, Liv Cristina; Quitzan, Juliany Gomes (Acta Scientiae Veterinariae, 2017)
Background: Lymphangiosarcoma (LSA) is a rare, highly malignant and infiltrative neoplasm of the lymphatic endothelium of dogs and cats. It is mostly reported in medium to large breed dogs, over 5-year-old, with no sexual predisposition. Affected animals present fluctuating and diffuse swelling, covering both dermis and subcutaneous tissue, spreading through lymphatic and haematic vessels. Histologically, LSA is characterized by connected channels devoid of conspicuous haematic elements. Treatment depends on location of the neoplasm, staging, and possibility of curative surgical excision. Chemotherapy and radiotherapy can increase survival time. In this report, we describe a rare case of vulvar LSA in a dog. This is the first Brazilian report of LSA in dogs so far. Case: A 3-year-old, female, mixed breed dog was presented for evaluation of vesicle-bullous lesions in the vulvar and perivulvar region with progressive growth along 6 month. Histopathology revealed neoplastic proliferation in the superficial dermis, advancing through the profound dermis. The histological lesion pattern was consistent with angiosarcoma, which united along with macroscopic pattern of the tumor, and the presence of multiple anastomosed vascular structures without erythrocytes within it at microscopy, was compatible with LSA. No evidence of metastasis or lymphadenopathy was found on survey radiography and ultrasound. We performed a surgical excision, and remaining wound was reconstructed with an advancement skin flap. Despite wide surgical resection, neoplastic cells could be found in surgical borders, as well as a metastatic inguinal lymph node. Postoperative chemotherapy based on doxorubicin as a single agent was administrated. Disease free interval (DFI) was one month after surgery, when small bullous lesions were observed near the surgical site, and histopathological exam confirmed LSA. Three months after the surgical procedure, the patient presented with worsening of the lesions, anorexia, and apathy. The owner opted for euthanasia. Total survival time was five months. Discussion: The LSA occurs often in dogs above five years old, unlike this case, in which the patient was 3 years old. Several anatomic locations were cited in other reports. In this case, the lesion was in both the vulvar and perivulvar regions, which is an uncommon location of LSA, described as secondarily affected region in one report only. Despite absence of metastasis in this case, lungs, kidneys, bone marrow, and spleen can be affected. Histopathologic exam is the golden standard for a definitive diagnose of LSA. Diagnosing LSA may be challenging due to its resemblance to hemangiosarcoma, and confirmation is only possible if histopathology detects an absence of red blood cells in the lymphatic channels. Prognosis is poor due to LSA aggressive and infiltrative features. Doxorubicin demonstrated good clinical response in other dogs. Chemotherapy protocols, whether alone or in combination with cyclophosphamide, have been proving to be promising in dogs with soft tissue sarcomas, such as LSA. Surgical approach is the most appropriate and it may be associated with radiotherapy or chemotherapy, especially if complete resection of the tumor is not possible. In this report, even though it was a young animal, the location and extension of the lesion did not contribute to the good prognosis, even after adding adjuvant chemotherapy to the treatment.